Measuring the quality of services provided by Mobily and its impact on the satisfaction of the pilgrims - Alosaimi, Saleh Matrouk Hamed (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to identify the impact of the quality of services provided by Mobily on the satisfaction of the pilgrims. The descriptive and analytical approach was used. The study tools were the questionnaire as a tool for collecting data and information, the study population consisted of the guests of Rahman, and a simple random sample was selected, amounting to 120 individuals from the guests of Rahman. The results of the study found that the services provided by Mobily to the pilgrims reached an arithmetic average of 3.97, which means that the relative weight is 79.34%, and this indicates that there is acceptance by the sample members on the scale of the quality of services provided by Mobily to the pilgrims in general. The existence of a statistically significant correlation between the quality of services provided by Mobily and the satisfaction of the pilgrims. The independent variables affecting the satisfaction of the pilgrims are (response, safety, empathy), and there is no effect of the rest of the variables. The study recommended that the company should conduct continuous evaluations of the pilgrims to ensure that the service provided is an ideal service. Conducting a comparative study between Mobily and other competing companies to ensure the quality of services provided and the level of customer satisfaction, to achieve a sustainable competitive advantage between companies. Paying attention to the suggestions provided by customers, as well as working to solve their problems and paying attention to the services they desire, and working hard.
Keywords: Quality of services; Mobily Company; guests of Rahman